2016
DOI: 10.7763/ijesd.2016.v7.807
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Composition of Fe, Mn and Al at 8 Different Profiles of Solid Waste Disposal Areas in Malaysia

Abstract: Abstract-Solid waste is a major issue in environmental management as it was generated by almost every single person in the world. In Malaysia, it is estimated 0.8 kg solid waste dumped by one person in rural area and 1.5 kg by person in urban area in a day. Landfill as a final waste disposal point is currently in critical number where it keeps on increasing every year. The most serious issues is landfill may cause air, water and soil pollution as waste disposed at landfill may produce leachate through water ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…The results of the water quality analysis showed that the coliform concentration at all sampling points exceeded the quality standard [12]. Based on the results of Total Coliform measurements in sample one, the results were obtained at 230; in sample two, the results were obtained at 91, and in sample three, the results were obtained at 230.…”
Section: Total Coliformmentioning
confidence: 94%
“…The results of the water quality analysis showed that the coliform concentration at all sampling points exceeded the quality standard [12]. Based on the results of Total Coliform measurements in sample one, the results were obtained at 230; in sample two, the results were obtained at 91, and in sample three, the results were obtained at 230.…”
Section: Total Coliformmentioning
confidence: 94%